Przechodzenie ojko- i anojkonimów w obrębie klas toponimicznych – na materiale z powiatu tureckiego - Zając, Ewelina (Nazwy terenowe i miejscowe w przestrzeni fizycznej, 2016)
The topic of the article are modern oyco- and anoyconymes of Turek district collected during field exploration. Historical material was also included to show changes taking place in toponimic classes over the years. Local and field names are categories of proper names that continue to appear but also disappear. Basing on the materials included in this work, the process of disappearance of local names can be observed as well as inclusion of smaller villages into larger settlements. Thus the character of the name remains the same, it is still an oyconym, but its function changes. The reverse process can also be observed, meaning the change of name character from oyconyme to anoyconyme, as the names of former villages are currently used for physiographic uninhabited objects. Processes related to creation of topographic names and shifting of oyco- and anoyconymes are supported with rich naming material. The article concludes by statement that mutual shifting of nomen apellativum and nomen proprium has cultural, not linguistic character, as the changes do not affect the system; character of names does not change, but their function does.